Feather regeneration as a model for organogenesis. (7th January 2013) - Lin, Sung‐Jan; Wideliz, Randall B.; Yue, Zhicao; Li, Ang; Wu, Xiaoshan; Jiang, Ting‐Xin; Wu, Ping; Chuong, Cheng‐Ming
<x xml:space="preserve">Abstract</x> In the process of organogenesis, different cell types form organized tissues and tissues are integrated into an organ. Most organs form in the developmental stage, but new organs can also form in physiological states or following injuries during adulthood. Feathers are a good model to study post‐natal organogenesis because they regenerate episodically under physiological conditions and in response to injuries such as plucking. Epidermal stem cells in the collar can respond to activation signals. Dermal papilla located at the follicle base controls the regenerative process. Adhesion molecules (e.g., neural cell adhesion molecule (NCAM), tenascin), morphogens (e.g., Wnt3a, sprouty, fibroblast growth factor [FGF]10), and differentiation markers (e.g., keratins) are expressed dynamically in initiation, growth and resting phases of the feather cycle. Epidermal cells are shaped into different feather morphologies based on the molecular micro‐environment at the moment of morphogenesis. Chicken feather variants provide a rich resource for us to identify genetic determinants involved in feather regeneration and morphogenesis. An example of using genome‐wide single nucleotide polymorphism (SNP) analysis to identify alpha keratin 75 as the mutation in frizzled chickens is demonstrated. Due to its accessibility to experimental manipulation and observation, results of regeneration can be analyzed in a comprehensive way. The layout of time dimension along the distal (formed earlier) to proximal (formed later) feather axis makes the morphological analyses easier. Therefore feather regeneration can be a unique model for understanding organogenesis: from activation of stem cells under various physiological conditions to serving as the Rosetta stone for deciphering the language of morphogenesis.